RI 4805 Production, Consumption, And Use Of Fuels And Electric Energy In The United States In 1929, 1939, And 1947 - William H. Lyon (The National Institute for Occupational Safety and Health (NIOSH), 1951)
In 1950 the Program Staff of the Department of the Interior undertook an exploratory study in the projection of energy requirements of the nation. This work was reported in Bureau of Mines Information Circular 7582 by H. J. Barnett. In that preliminary study Mr. Barnett, after exploring the nature of the energy economy in some detail, evolved a method for estimating how much energy will be required in the future, based on estimates of trends in efficiency of energy utilization in specific applications, the physical output of specific energy-consuming industries, size of the population, productivity advances in the economy at large, consumer preferences, and other factors. Considerable new information was developed regarding the nature of energy demands and the possible levels of requirements for each fuel under various assumed business conditions. The study analyzed the interrelationships, including substitutions, among the fuels and emphasized the need for viewing the energy economy as an integrated albeit complex whole. This exploratory study showed a need for a single comprehensive statistical re-port that would assemble and show in a uniform manner the diverse published statistical data on energy commodities now scattered through many publications. A particularly important need was for a set of historical statistics showing the production and consumption of all energy on a B.t.u. basis. As the prospective size and nature of the future energy requirements of the nation are matters of continuing importance, this report was prepared to assist further investigations of the subject. In this report the authors undertake to assemble and present in tabular form, on a uniform basis, the production and use of each of the fuels and electric energy in the United states for three census years -1929, 1939, and 1947. The year 1947, rather than a later year, was selected because it is the most recent year for which census data are available showing the consumption of fuel by each of the manufacturing industries. It is hoped that making data for these 3 years available in one re-port will provide the needed statistical background for further studies of fuel requirements and supplies.